The virtual museum as a strategy for teaching history. - Jiménez Morales, Leoncio (2013)
The article proposes a strategy for teaching history, which the author has termed virtual museum. The discussion focuses on four topics: 1) the crisis surrounding history teaching, 2) the historical relationship school-museum, 3) educational virtual technology, and 4) the virtual museum: a proposal for an integrated curriculum.